ANALISIS RESEPSI PEGAWAI STARBUCKS FILATELI TENTANG VIDIO BLOGGING JOKO WIDODO SEBAGAI GAYA KOMUNIKASI BARU PRESIDEN INDONESIA DI ERA MEDIA BARU - Taqwa Sejati (Jurnal Public Relations (J-PR), 2020)
This research sees the reality of developing media social technology which it's also used by our president Joko Widodo to record all of the activity while the President on the national duty or not. With his smartphone he uploaded his video to his private account. President Jokowi's hobby of vlogging affects so many people from local to international with posting a positive and negative comment on it. People's perception are different and various on President Jokowi's vlog, remembering every receiving message process there will be always a wall of culture, knowledge, and experience of the message receiver